Electrovectorcardiographic study of left ventricular aneurysm in ischemic heart disease - Varoni, Leonardo Paschoal Camacho; Samesima, Nelson; Facin, Mirella; Filho, Horácio Gomes Pereira; Madaloso, Bruna Affonso; Junior, Wilson Mathias; Pastore, Carlos Alberto (Frontiers in Cardiovascular Medicine, 2023)
The aim was to characterize the electrovectorcardiographic pattern of ventricular aneurysms in ischemic cardiopathy by analyzing the cardiac ventricular repolarization. The medical records of 2,670 individuals were analyzed in this cross-sectional study. A test phase included 33 patients who underwent transthoracic echocardiogram with ultrasonic enhancing agent, electrocardiogram, and vectorcardiogram (aneurysm group -n=22, and akinesia group -n=11). In the validation phase, cardiac magnetic resonance imaging established the left ventricle segmental contractility in 16 patients who underwent electrocardiographic and vectorcardiographic tests (aneurysm group, n=8, and akinesia group, n=8).The variables studied were the presence of the T-wave plus-minus pattern and the T-wave loop anterior-posterior pattern in V2, V3, and V4. The diagnostic indices used were sensitivity, specificity, and predictive values, with their respective 95% confidence intervals. During the test and validation phases, the analysis of the presence of the T-wave plus-minus pattern identified the aneurysm group with a sensitivity of 91% vs. 87% and specificity of 91% vs. 87% (p<0.0001 vs. p=0.01), respectively. Meanwhile, the T-wave loop anterior-posterior pattern evidenced sensitivity of 95% vs. 77% and specificity of 91% vs. 87% (p<0.0001 vs. p=0.04), respectively. The electrovectorcardiographic parameters showed high accuracy for recognizing left ventricular aneurysms in ischemic heart disease.